Globalisation des migrations internationales : dynamiques et modalités. Une contribution réflexive à partir du cas israélien - William Berthomière (Revue des Mondes Musulmans et de la Méditerranée)
International migration studies constitute one of the most interesting mirrors of the globalization process. Much research carried out in this field highlights the diversity of the social structures elaborated notably through more and more complex circulation practices. Even if this is not really a new phenomenon, the scale and volume of the migration trends are changing the social fabric of both the homelands and the host countries. In this part of the process, the effect of the resistance of the More Developed Countries to promote migration policies in accordance with the circulatory migration scheme was to draw new countries into the International Migration System (IMS). Some of the most important case studies are offered by the Mediterranean countries confronted with South-North migration flows. Some situations reflect the tension created by the extension of the borderlines of Schengen Europe, as can be observed in the Ceuta and Melilla cases and others which indicate a process of inclusion of new countries in the IMS. Israel is one of the countries that are today concerned by this inclusion.This article aims at exploring this social phenomenon, new for the Israeli society. This case confronts us to a social process based on a combination of internal and external factors reinforced by globalization. The responses of migrant workers and of the society illustrate perfectly the questions raised by what is commonly defined as the confrontation of the global to the local. The idea is to explore this “dilemma” and by doing so, to take part in the debate concerning the Transnational stance.